Unusual Ant Hosts of the Socially Parasitic Ant Anergates atratulus (Schenck, 1852) (Hymenoptera, Formicidae) - Albena Lapeva-Gjonova; Kadri Kiran; Volkan Aksoy (Psyche: A Journal of Entomology)
The extreme inquiline ant Anergates atratulus (Schenck, 1852) (Hymenoptera, Formicidae) was collected in ant nests of Tetramorium moravicum Kratochvil, 1941 in Bulgaria and of T. chefketi Forel, 1911 in Bulgaria and Turkey. The reported ant hosts belong to the Tetramorium chefketi species complex in contrast with the typical hosts from Tetramorium caespitum/impurum complex. This finding confirms the assumption that a broader range of host species for the socially parasitic species A. atratulus may be expected. Present data on the new host species expand knowledge about biology of this rare ant species, included in the IUCN Red List of threatened species.